Comprehensive wood dwelling tests for Post-and-Beam and Shear-Wall structures reflecting foundation boundaries - Takaya, Kazuki; Ota, Kazuto; Yenidogan, Cem; Takahashi, Takehiro; Yamada, Shohei; Kashiwa, Hisatoshi; Kawamata, Yosuke; Hayashi, Kazuhiro; Nagae, Takuya (WILEY, 2024)
This paper focuses on the ultimate state of three-story wood dwellings with high aspect ratios, which are increasing in Japan's urban areas. Using shaking table test results from the 2019 full-scale shaking table test, a comprehensive study is conducted on the accuracy of evaluating ultimate state through the story shear failure mode at the first story, the tension fracture mode at the wall base of the first story, and foundation sliding mode on the soil. Methods evaluating the dynamic response behaviors of the building systems are also investigated. In the test, the current Japanese seismic design guidelines were applied, and two Grade-3 buildings were prepared. One adopted the Post-and-Beam structure (A-building), and the other the Shear-Wall structure (B-building). A series of tests planned very different physical boundary conditions surrounding their reinforced concrete (RC) mat foundations. The sills, column bases and wall bases of the upper wood structures were anchored to the RC foundations by steel anchor bolts, according to the current Allowable Stress Design (ASD) requirements. In the first stage, A-building equipped a Base-Isolation system, while B-building represented a generic foundation constructed on a 1.5 m-height real soil ground by preparing a rigid soil box (Foundation-Soil system). In the second stage of A-building and B-building, the foundation was firmly fixed (Fixed-Foundation system), and shaking table motions were fully applied to the foundations. The entire test system was setup on the large shaking table facility at E-Defense, and a series of tests were conducted using JMA-Kobe motion and JR-Takatori motion recorded in the 1995 Kobe earthquake as Maximum-Considered-Earthquake motions. Confirmed was the change in the structural mechanism due to the upper structural systems and the foundation boundaries. Regarding the upper wood structure performance in the Fixed-Foundation system, a story shear failure mode was observed at the first story in A-building, while a tension fracture mode at the base of the first story in B-building. This difference of failure mode is difficult to determine with ASD. The maximum strength were more than four times higher than the ASD base shear force. Tension fracture capacity at the wall base was mainly enhanced by the presence of the steel anchor bolts. Regarding the foundation performance in Foundation-Soil system of B-building, a horizontal displacement up to 240 mm was observed between the foundation and soil when JMA-Kobe 100% was applied. A response reduction effect was observed in the upper wood structure, similar to the Base-Isolation system of A-building. The initial friction and cyclic friction strength capacities between the foundation and soil were quantitatively evaluated considering the horizontal two-directional sliding. The representative test results were converted to the corresponding SDOF systems based on the first mode response assessment. In the Fixed-Foundation system, the dynamic response characteristics of the upper wood structures were properly represented using Ibarra-Medina-Krawinkler pinching model in the equivalent SDOF system. This paper addresses the changes in structural mechanisms given by the upper wood structural system and the boundary conditions surrounding foundation in the Maximum-Considered-Earthquake, based on the 2019 full-scale shaking table test results for wood dwelling, and methods evaluating the dynamic responses of the building systems are also investigated. In the Fixed-Foundation system of Post-and-Beam structure unlike Shear-Wall structure, the dynamic response characteristics of the upper wood structures were properly represented using Ibarra-Medina-Krawinkler-pinching Model in the equivalent SDOF system. The peak points taht is, the maximum acceleration and displacement of the SDOF systems were consistent with the Sa-Sd spectrum of the input motions, regardless of the difference of the Base-Isolation, Foundation-Soil, and Fixed-Foundation systems. image
Keywords: base isolation; foundation sliding; shaking table test; soil ground; ultimate strength; wood dwelling; HYSTERETIC MODELS; Engineering